Analisis Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Toko Kang Cuci Sepatu - Fitrianingsih Fitrianingsih; Arwanda Siddik; Farhan Abdillah; Refy Ananda Gulo; Rendi Rivaldi; Siti Sakdiah Rangkuti (Management And Business Progress, 2025)
This study aims to determine the effect of product quality and service quality on customer satisfaction at the Kang Cuci Sepatu store in BP7. Increasingly fierce competition in the shoe laundry business demands that businesses improve product and service quality to maintain customer loyalty. Data were collected through a questionnaire measuring customer perceptions of product quality, service quality, and customer satisfaction. The results showed that the majority of respondents rated the product quality, specifically the shoe washing results, as excellent, and the service was friendly and responsive. Service turnaround times were also assessed as consistent with promises made. Overall customer satisfaction was high, with many customers willing to use the service again and recommend it to others. Therefore, the Kang Cuci Sepatu store is advised to continue maintaining and improving product and service quality, particularly in terms of service speed, communication, and physical facilities, to maintain and increase customer satisfaction and loyalty amidst increasingly competitive business conditions.